2013
DOI: 10.1155/2013/548246
|View full text |Cite
|
Sign up to set email alerts
|

Drought Tolerance in Modern and Wild Wheat

Abstract: The genus Triticum includes bread (Triticum aestivum) and durum wheat (Triticum durum) and constitutes a major source for human food consumption. Drought is currently the leading threat on world's food supply, limiting crop yield, and is complicated since drought tolerance is a quantitative trait with a complex phenotype affected by the plant's developmental stage. Drought tolerance is crucial to stabilize and increase food production since domestication has limited the genetic diversity of crops including wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
124
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(128 citation statements)
references
References 101 publications
(141 reference statements)
3
124
0
1
Order By: Relevance
“…Several previous studies showed that there was a reducing of vegetative growth and a producing organs assimilate (Anjum, Xie, & Wang, 2011). The decrease of photosynthesis rate due to the decline of CO2 exchange the surface of leave, as the consequence for reducing of assimilate production (Budak, Kantar, & Yucebilgili Kurtoglu, 2013). Thus, the results of the experiment indicates that each line of wheat show different morphological changes in term of vegetative growth and yield as well.…”
Section: Resultsmentioning
confidence: 79%
“…Several previous studies showed that there was a reducing of vegetative growth and a producing organs assimilate (Anjum, Xie, & Wang, 2011). The decrease of photosynthesis rate due to the decline of CO2 exchange the surface of leave, as the consequence for reducing of assimilate production (Budak, Kantar, & Yucebilgili Kurtoglu, 2013). Thus, the results of the experiment indicates that each line of wheat show different morphological changes in term of vegetative growth and yield as well.…”
Section: Resultsmentioning
confidence: 79%
“…Global climate change presents a major threat to wheat production and productivity, particularly due to increased drought frequencies and intensities, hence, the need to breed drought tolerant and better adapted varieties for the changing environments (Budak et al, 2013). Possibly, the susceptibility of modern wheat varieties to water stress is magnifying the effects of drought on the crop's poor production and productivity under severe drought-stress condition.…”
Section: Discussionmentioning
confidence: 99%
“…Drought tolerance can be estimated by the mode, timing, and severity of the dehydration stress and its occurrence with other abiotic and biotic stress factors [7,8]. To counter adverse effects of different environmental stresses, plant have evolved special mechanisms and undergone a serial of physiological changes, but the "cross-talk of stresses" and "cross-tolerance to stresses" have not been extensively explored [9]. Crop genotypes having potential tolerance for environmental stresses is a common approach for improvement of crop productivity [10].…”
Section: Introductionmentioning
confidence: 99%